Optimalisasi Pemanfaatan Ikan Manyung Asap Menjadi Abon Ikan Manyung Dalam Upaya Pencegahan Stunting Di Kelurahan Pasarbatang Brebes - Gunawan, Adhi; Setiawan , Andi; Ayu Qotrun Nada, Diah; Mayan Fauni, Eni; Charyani, Inda; Yusuf, Iwan; Oktasani, Nafaati; Ratnasari, Nor Indah; Dewi Trisnawati, Qori; Nugroho, Suryo; Aditya, Tirta (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Tanah Laut (Politala), 2024)
Stunting is a condition of malnutrition in toddlers that occurs due to limited access to food in a family, causing the individual's body to not fulfill nutritional intake. In addition to ensuring nutritional value, the safety aspect of food content is one of the factors for indirect editing. The use of local food that is safe and has good nutritional content can be an alternative in overcoming a family and individual limitations in innovating nutritious food. One of the existing potentials is the existence of smoked fish SMEs in RW 9 Pasarbatang Village which can be innovated into a sea catfish floss. The purpose of community service is to increase knowledge of the Pasarbatang sub-district community in utilizing the local food potential of smoked sea catfish into shredded sea catfish as an alternative food to prevent stunting. The method implemented in this community service istransfer knowledge Then in the introduction stage to the community, an audience was carried out and the handing over of the booklet to the Pasarbatang Kelurahan so that in the future it could be further socialized regarding stunting prevention food innovations to the Pasarbaatang Kelurahan Community. The result of this service is that the Pasarbatang Village knows about food innovations that can be developed from existing MSMEs so that local processed food innovations for smoked catfish become an alternative food for stunting prevention, namely shredded sea catfish.